Farinha de chia (Salvia hispânica L.) parcialmente desengordurada como fonte de ácidos graxos para pães sem glúten - Ewerling, Marci (2016)
The chia seed (Salvia hispanica L.) has attracted a great interest of the food industry for its nutritional characteristics. Thus, this study aimed to prepare bread gluten-free, assessing the influence of the addition of partially defatted chia flour (PDCF), and xanthan gum and hydroxypropyl methylcellulose gum (HPMC), in the rheological characteristics, physico-chemical and sensory characteristics of bread. Thus, a central composite rotational design was used (CCRD), type 23 to investigate the influence of omega-3 content, total fat, crude protein and total carbohydrates. Within the ranges studied for the three variables, it was possible verify that the addition of PDCF promoted greater contribution to mathematical models, which calculated R2 allowed to explain 94 % of the phenomena occurring in the investigated range. Through the desirability analysis it was found that the formulation of the central point converged on optimizing for the three variables. At the acceptance test for the sample containing 20 % PDCF, texture attribute was better evaluated; the attributes aroma, flavor and overall appearance did not show a larger or smaller acceptance. For PDCF, elevated protein (30.15 %) and carbohydrates (41.60%) levels were found, and water absorption capacity of 10.53 g g-1 of sample, this value being half of that found for the chia integral flour (20 g g-1 of sample). PDCF showed high levels of omega-3 (60 %) and omega-6 (24 %). The use of PDCF and gums was promising in the development of gluten-free bread with good sensory and nutritional characteristics.